RNA Interference Prevents Autosomal-Dominant Hearing Loss - Shibata, Seiji B. (Am J Hum Genet, 2016)
Hearing impairment is the most common sensory deficit. It is frequently caused by the expression of an allele carrying a single dominant missense mutation. Herein, we show that a single intracochlear injection of an artificial microRNA carried in a viral vector can slow progression of hearing loss for up to 35 weeks in the Beethoven mouse, a murine model of non-syndromic human deafness caused by a dominant gain-of-function mutation in Tmc1 (transmembrane channel-like 1). This outcome is noteworthy because it demonstrates the feasibility of RNA-interference-mediated suppression of an endogenous deafness-causing allele to slow progression of hearing loss. Given that most autosomal-dominant non-syndromic hearing loss in humans is caused by this mechanism of action, microRNA-based therapeutics might be broadly applicable as a therapy for this type of deafness.